Matches and Mismatches Between Global Conservation Efforts and Global Conservation Priorities - Willer, David F.; Smith, Kevin; Aldridge, David C. (Frontiers in Ecology and Evolution, 2019)
Species extinctions are occurring 1000 times faster than background rates and conservation efforts must focus limited resources on prioritised threats and habitats. The IUCN Red List has assessed extinction risk for over 91,000 species, also recording their Habitats occupied and the Threats each species is exposed to. To protect biodiversity conservation organisations mobilise funds; effort realised in staff time, research and public engagement. There is need to understand whether global conservation effort is distributed appropriately across Threats and Habitats to protect the greatest number of high extinction risk species. In this study three major measures of global conservation effort across Red List Threats and Habitats were assessed; staff time spent by the largest cluster of conservation organisations in the world - Cambridge Conservation Initiative, efforts by international NGOs through social media, and global conservation research publications since the year 2000. We find global conservation effort is generally aligned with global conservation priorities, but there are important outliers. Shrublands and rocky areas receive disproportionately little investment across all effort measures relative to the number of high extinction risk species, threats from residential and commercial development receive relatively low research and time investment despite social media attention, while marine areas and climate change receive more attention than expected. Governments and society must make critical conservation decisions in the context of rapid global change, and there is potential for key Threats or Habitats to receive less attention than required. The global conservation community would be wise to carefully consider and improve its understanding of effort-priority mismatches if the greatest number of high extinction risk species are to be protected.